PERTANGGUNG JAWABAN ORANGTUA TERHADAP ANAK YANG BEKERJA UNTUK MEMBANTU PEREKONOMIAN KELUARGA PERSPEKTIF MAQASHID SYARIAH DAN UU NO 35 TAHUN 2014 PERUBAHAN ATAS UU NO 2002 TENTANG PERLINDUNGAN ANAK (Studi Kasus di Kecamatan Seteluk Kabupaten Sumbawa Barat) - Sherina Pramasela; Hery Zarkasih (Al-IHKAM Jurnal Hukum Keluarga Jurusan Ahwal al-Syakhshiyyah Fakultas Syariah IAIN Mataram, 2023)
This research was motivated by researchers' attention to the phenomenon of minors working as the backbone of the family in Seteluk District, West Sumbawa Regency. The type of method used is a qualitative method with a juridical-empirical research approach. The data collection methods used were observation and interviews. The researcher explains the form of parental coverage for children who work to help the family's economy in Seteluk District, West Sumbawa Regency, and uses children, parents, and village and sub-district governments as primary data sources. Data collection techniques in this thesis are observation and interviews. The data that has been collected is then analyzed and conclusions are drawn. The results of this research are the first form of parental coverage for children who work to help the family economy in Seteluk District, West Sumbawa Regency, namely providing a living and good nutrition, giving education rights to some working children, and giving children the right to participate.